Experimental investigation of mono and hybrid GNP - MWCNT nano-enhanced phase change materials for thermal energy storage applications - Gungor, Sercan Gulce; Martinez, Franklin R.; Borri, Emiliano; Gasa, Gemma; Esen, Mehmet; Cabeza, Luisa F. (Elsevier, 2026)
This study aims to examine the effect of carbon-based nanoparticles of different sizes and morphologies, which are 2D graphene nanoplatelets (GNPs) and 1D multi-walled carbon nanotubes (MWCNTs). These are used in mono and hybrid forms to investigate the thermal properties of n-octadecane, an organic phase change material. The thermal conductivity, latent heat, and phase change temperature of nano-enhanced phase change material (NePCM) samples are analyzed at different concentrations ranging from 0 to 2.5% by weight. Improvements in thermal conductivity values are 22.3% and 52.3% when MWCNT and GNP are added separately, respectively, and 39.6% when adding the hybrid of GNP and MWCNT is added. Reductions in latent heat values are 5.8% and 5.7% when MWCNT and GNP are used separately and 6.6% when GNP + MWCNT are used together. The experimental measurement values are evaluated using statistical analysis and multi-objective optimization. According to the results, this optimization process identifies the most suitable NePCM sample.
Keywords: Nano-Enhanced Phase Change Material; N-Octadecane; Graphene Nanoplatelets; Multi-Walled Carbon Nanotubes; Thermal Properties